PEMBUKTIAN HORIZONTAL TRANSFER OF RESISTANCE GENES MELALUI UJI SENSITIVITAS ANTIBIOTIKA PADA BAKTERI GENUS Staphylococcus DARI KASUS BOVINE MASTITIS - Mustofa Helmi Effendi (The East Java Biological Society, 2008)
The experiment was carried out to show the evidence of horizontal transfer of resistance genes by antibiotics sensitivity test on bacteria of genus of Staphylococcus from bovine mastitic cases. The first step of the experiment was to prepare pure culture of Staphylococcus aureus and Coagulase Negative Staphylococci. Milk samples were collected from mastitic cases at the afternoon milking time. Preparation of pure culture of isolates were confirmed by MS agar, hemolytic activity, catalase and coagulase test. Both isolates were tested by using antibiotics sensitivity test. The result showed that the both isolates of Staphylococcus aureus and Coagulase Negative Staphylococci from Surabaya dairy herd were resistant against erythromycin antibiotic. Based on the result, it can be concluded that there was horizontal transfer of resistance genes between both isolates from same udder of dairy cows.